PENGEMBANGAN MEDIA MONOPOLI DENGAN TEMA INDAHNYA KERAGAMAN DI NEGERIKU PADA MATA PELAJARAN IPS KELAS IV - Lia Khaerunisa; Zerri Rahman Hakim; M. Taufik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the feasibility, how to get scores from experts, and the response of students from the media that the researchers are trying to develop, namely the SETAPARULA Monopoly (Weapons, Dance, Clothing, Houses, Songs) with the theme of The Beauty of Diversity in My Country. The research was conducted at SDN Panunggangan 1 with 10 fourth-grade students as the research subjects for limited trials. The type of the research used in the Research and Development method was indicated by Borg and Gall modified from Sugiyono, which consisted of 6 stages, problem analysis, data collection, product design development, product design validation, an improvement test (revision) product design, and product testing stages. The instrument used was a questionnaire sheet for expert validation and students‟ responses. The results of the validation test by experts (media experts, material experts, linguists, and education experts) on the quality of the developed monopoly media were categorized in the appropriate criteria with an assessment percentage of 78.21%. The results of a limited trial for students on monopoly media obtained very decent criteria with an assessment percentage of 100%. Based on the results of the study, it could be concluded that the monopoly media developed was very suitable to be used in the learning process of Social Sciences learning subject (IPS).